KEMAJUAN PENELITIAN BIOSINTESIS MONOTERPENA DAN PERANAN Terpene Cyclase: Suatu Kajian Pustaka - Dalengkade, Mario Nikolaus; Fredy, Ferry (Jurnal Biologi Udayana; Vol 22 No 2 (2018): JURNAL BIOLOGI UDAYANA, 2018)
Chain extension, bond?? termination, and rearrangement of C bonds from complex reactions by cyclase create a universal substrate for C 10 biosynthesis. From this substrate it consumes abundant C 10 in nature. Approved by the researcher as a postulate. Mechanical and genetic studies also prove the postulate. In addition, metal ions as a binder play an important role in C 10 biosynthesis and its regulation.